2021
DOI: 10.1016/j.ajog.2020.11.042
|View full text |Cite
|
Sign up to set email alerts
|

Population attitudes toward contraceptive methods over time on a social media platform

Abstract: BACKGROUND: Contraceptive method choice is often strongly influenced by the experiences and opinions of one's social network. Although social media, including Twitter, increasingly influences reproductive-age individuals, discussion of contraception in this setting has yet to be characterized. Natural language processing, a type of machine learning in which computers analyze natural language data, enables this analysis. OBJECTIVE: This study aimed to illuminate temporal trends in attitudes toward long-and shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 33 publications
2
25
0
1
Order By: Relevance
“…Nevertheless, negatively oriented comments had a strong presence among the open responses, overall. This is in correspondence with previous research noting negative attitudes toward the copper IUD (14,16,18,20,21), although positive experiences and attitudes have also been shown (6,14,15,23).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, negatively oriented comments had a strong presence among the open responses, overall. This is in correspondence with previous research noting negative attitudes toward the copper IUD (14,16,18,20,21), although positive experiences and attitudes have also been shown (6,14,15,23).…”
Section: Discussionsupporting
confidence: 92%
“…While research points to high levels of satisfaction with LARC methods including the copper IUD (6,14,15), studies have also indicated negative attitudes toward the copper IUD in countries including Sweden (14,(16)(17)(18)(19)(20)(21). Negative views on the copper IUD have often been associated with communication in social networks, including online social media, where negative commentaries on IUDs have been found to be prevalent (14,16,(22)(23)(24)(25)(26)(27), although positive views are also communicated (23,25). Meanwhile, the strong importance of social networks for contraceptive choice and use has been observed in countries including Sweden (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that negative entries usually employ more emotional words (specifically when trying to communicate fear), while more positive entries seem to be approved on Facebook. In a different study ( 17 ), on short- and long- term contraceptive methods, online trends using tweets between March 2006 and December 2019, were examined. Relevant tweets were tracked, using search terms of generic or brand names, colloquial names and abbreviations.…”
Section: Resultsmentioning
confidence: 99%
“…Mann-Kendall (MK) [23] is a non-parametric test, which is widely used to detect monotonic trends in a time-series. Its robustness against censored and non-Gaussian distributed data o time series with missing or noisy observations [5] that are frequently encountered in a term occurrence time series makes MK an almost standard trend test method in NLP [1,[6][7][8][9][10][11][12]. A brief description of the MK method is provided below.…”
Section: Mann-kendall Trend Test With Sen's Slope Estimatormentioning
confidence: 99%
“…Due to their reduced sensitivities to outliers [2], the lack of assumptions concerning the data sample distribution [3] or homoscedasticity [4], nonparametric trend tests tend to be favored by researchers over parametric methods. In particular, the Mann-Kendall (MK) test statistic being a robust trend indicator when dealing with censored data, arbitrary non-Gaussian data distributions or time series with missing observations [5] have become almost standard methods for NLP applications [1,[6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%